The Implications Of The Scheduled Tribes and Other Traditional Forest Dwellers (Recognition Of Forest Rights) Act, 2006 - Singh, Shivalika (Indian Forester, 2014)
The Scheduled Tribes and Other Traditional Forest Dwellers (Recognition of Forest Rights) Act, 2006 has emerged as an amalgamation of multifarious interests spread across the country in the form of new institutional settlement. The objective of the study was to highlight the problems being faced by the executing agencies due to the ambiguities in the Act. In the present paper results of a study carried out in Kathoria village of Sehore district regarding implementation of Forest Right Act, 2006 have been discussed. Results indicate that the Act needs amendments in order to achieve the objects with which it was initially set up and to clarify the ambiguities that have crept in during the course of its implementation.